(untitled) (European Journal of Interdisciplinary Research and Development, 2026)
This study investigates the effectiveness of a context-based instructional model for developing pragmatic competence among non-philological university students in English for Specific Purposes (ESP) contexts. The research is based on a quasi-experimental design involving 483 students from three higher education institutions, divided into control and experimental groups. The study was conducted in three stages: diagnostic analysis, instructional intervention, and final evaluation. The proposed methodology integrates contextualization, scaffolding, communicative-cognitive strategies, and task-based learning, supported by digital tools and AI-based feedback systems. Data were collected through diagnostic tests, discourse completion tasks, role-play simulations, questionnaires, and classroom observations. The results demonstrate significant improvements in the experimental group across pragmalinguistic, sociopragmatic, and strategic-communicative competencies, while the control group showed minimal progress. Statistical analysis using Student’s t-test confirmed the significance of the observed differences. The findings suggest that pragmatic competence develops most effectively through contextualized, interactive, and reflective learning environments. The study contributes to the field by proposing an integrative methodological framework that bridges the gap between linguistic knowledge and real-world communication. It also highlights the role of digital technologies in enhancing metapragmatic awareness and supporting learner autonomy.